PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PEER LESSONS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI ALAT-ALAT OPTIK DI MTsN ANDALAN PEKANBARU - Mely Janiati Riski; Azizahwati '; Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the result of increased student learning material optical devices through the implementation of cooperative learning modelpeer lessons in MTsN Andalan Pekanbaru. Samples are VIII.9 class as an experimental class and the class as a class VIII.2 controls. The study was conducted in MTsN Andalan Pekanbaru from March to May 2016, for 3 months. This research was Quasi Experimental design using the pretest-posttest control group design. Data collection instrument in this study was pretest and posttest cognitive learning outcomes that are 20 questions. Data were analyzed descriptively include absorption, the effectiveness of learning, mastery learning, and improved learning outcomes. Analysis of the data after learning the implementation of cooperative learning model peer lessons got good results. The average absorption in class experiments using peer application of lessons is 80.71% effective with the category average of 80% completeness study with very good categories, and improved learning outcomes by 0.66 in the medium category. Therefore peer lessons cooperative learning model effectively used in learning and can improve student learning outcomes in the material optical instruments in MTsN Andalan Pekanbaru.Keywords: Cooperative Learning, Peer Lessons, Cognitive Learning Outcomes